Occupational and Public Exposure During Normal Operation of Radioactive Waste Disposal Facilities - M. V. Vedernikova; I. A. Pron; M. N. Savkin; N. S. Cebakovskaya (Радиационная гигиена)
This paper focuses on occupational and public exposure during operation of disposal facilities receiving liquid and solid radioactive waste of various classes and provides a comparative analysis of the relevant doses: actual and calculated at the design stage. Occupational and public exposure study presented in this paper covers normal operations of a radioactive waste disposal facility receiving waste. Results: Analysis of individual and collective occupational doses was performed based on data collected during operation of near-surface disposal facilities for short-lived intermediate-, lowand very low-level waste in France, as well as nearsurface disposal facilities for long-lived waste in Russia. Further analysis of occupational and public doses calculated at the design stage was completed covering a near-surface disposal facility in Belgium and deep disposal facilities in the United Kingdom and the Nizhne-Kansk rock massive (Russia). The results show that engineering and technical solutions enable almost complete elimination of internal occupational exposure, whereas external exposure doses would fall within the range of values typical for a basic nuclear facility. Conclusion: radioactive waste disposal facilities being developed, constructed and operated meet the safety requirements effective in the Russian Federation and consistent with relevant international recommendations. It has been found that individual occupational exposure doses commensurate with those received by personnel of similar facilities abroad. Furthermore, according to the forecasts, mean individual doses for personnel during radioactive waste disposal would be an order of magnitude lower than the dose limit of 20 mSv/year. As for the public exposure, during normal operation, potential impact is virtually impossible by delaminating boundaries of a nuclear facility sanitary protection zone inside which the disposal facility is located and can be solely attributed to the use of public roads during radioactive waste transportation to the disposal facility site.